Analysis of deletional hereditary persistence of fetal hemoglobin/δβ‐thalassemia and δ‐globin gene mutations in Southerwestern China - Zhang, Jie (Mol Genet Genomic Med, 2019)
BACKGROUND: Deletional hereditary persistence of fetal hemoglobin (HPFH)/δβ‐thalassemia and δ‐thalassemia are rare inherited disorders which may complicate the diagnosis of β‐thalassemia. The aim of this study was to reveal the frequency of these two disorders in Southwestern China. METHODS: A total of 33,596 subjects were enrolled for deletional HPFH/δβ‐thalassemia, and positive individuals with high fetal hemoglobin (Hb F) level were diagnosed by multiplex ligation‐dependent probe amplification (MLPA). A total of 17,834 subjects were analyzed for mutations in the δ‐globin gene. Positive samples with low Hb A(2) levels were confirmed by δ‐globin gene sequencing. Furthermore, the pathogenicity and construction of a selected δ‐globin mutation were analyzed. RESULTS: A total of 92 suspected cases with Hb F ≥5.0% were further characterized by MLPA. Eight different deletional HPFH/δβ‐thalassemia were observed at a frequency of 0.024%. In addition, 195 cases suspected to have a δ‐globin gene mutation (Hb A(2) ≤2.0%) were characterized by molecular analysis. δ‐Globin gene mutation was found at a frequency of 0.49% in Yunnan. The pathogenicity and construction for a selected δ‐globin mutation was predicted. CONCLUSION: Screening of these two disorders was analyzed in Southwestern China, which could define the molecular basis of these conditions in this population.